2020
DOI: 10.3390/w12072047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CYGNSS Observations for Flood Detection and Mapping during Sistan and Baluchestan Torrential Rain in 2020

Abstract: Flood detection and produced maps play essential roles in policymaking, planning, and implementing flood management options. Remote sensing is commonly accepted as a maximum cost-effective technology to obtain detailed information over large areas of lands and oceans. We used remote sensing observations from Global Navigation Satellite System-Reflectometry (GNSS-R) to study the potential of this technique for the retrieval of flood maps over the regions affected by the recent flood in the southeastern part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…A potentially innovative data source for flood monitoring is investigated in [9]. GNSS reflectometry is a technique that uses microwave signals emitted by global positioning system constellations and collected by suitable receivers to gain information about (bistatic) reflectivity of the Earth's surface.…”
Section: Discussionmentioning
confidence: 99%
“…A potentially innovative data source for flood monitoring is investigated in [9]. GNSS reflectometry is a technique that uses microwave signals emitted by global positioning system constellations and collected by suitable receivers to gain information about (bistatic) reflectivity of the Earth's surface.…”
Section: Discussionmentioning
confidence: 99%
“…This method has also been widely used in previous studies using CYGNSS data to retrieve the submerged state of the surface. However, owing to the different parameters, such as the topography, roughness, and vegetation of the studied area, this threshold is not certain [40][41][42]. For instance, the threshold used by [40] was 12 dB for the medium-vegetation density and typical roughness.…”
Section: Sr Thresholdmentioning
confidence: 95%
“…Studies have shown that the results of the flooding area distribution obtained by CYGNSS are in good agreement with rainfall data, SMAP, and SMOS brightness temperature data. Rajabi et al [42] studied the feasibility of using CYGNSS data to detect and map flood distributions during heavy rains in Sistan and Baluchistan in 2020. The results show that the CYGNSS signal-to-noise ratio observation can be used to detect and map the distribution of a flood disaster, and the results are in good agreement with the flood disaster distribution obtained from MODIS optical images.…”
Section: Introductionmentioning
confidence: 99%
“…To compute CYGNSS reflectivity values, we only consider the strongest scattering power provided by natural land surfaces, which is received from the coherent part of the reflected signal [19,43]. In this sense, land surface reflectivity can be sensed from GNSS-R data through the bistatic radar equation for the coherent component of LHCP GNSS bistatic microwave signals [17,36,[44][45][46], which takes the following expression [20] when dealing with GNSS-R data:…”
Section: Methodsmentioning
confidence: 99%
“…The subscript lr stands for a scattering mechanism when the incident RHCP signal is scattered by the surface and inverts the polarization to LHCP at the receiver position. Γ lr is the surface reflectivity from which the SMC might be estimated, after correction of the noise floor component (N) in the DDM [31,46]. R t and R r are the transmitter and receiver range to the specular point, respectively.…”
Section: Methodsmentioning
confidence: 99%